The Effectiveness of Zakat Management at Desa Berdaya, Mekarwangi Village, Lembang - Nurhasanah, Neneng; Ramdan Hidayat, Asep; Hayatuddin, Amrullah; Efendi, Nur; Sukaeningsih, Nining; Nurul Fadhilah, Salma; Asiyah Nur Arifah, Siti (KnE Social Sciences, 2023)
Implementing productive zakat is still facing obstacles, including mustahiq who cannot be trusted in managing the business both operationally and mentally when receiving capital/money. Managing productive zakat is technically more difficult than distributing consumptive zakat, both in terms of procedures and responsibilities. Several studies also showed that the distribution of productive zakat funds did not significantly affect mustahiq’s profits and business income. Even if productive zakat affected the growth of mustahiq micro-enterprises, it did not affect their welfare. However, this did not dampen Rumah zakat as zakat manager to continue to develop productive zakat management. Desa Berdaya Program is a community empowerment process carried out by Rumah zakat Facilitator in a certain area and time, by helping to accelerate the improvement of existing problems in the area. This study aimed to analyze the success of Rumah zakat in managing zakat productively and its obstacles. This study used a qualitative method with an analytical descriptive approach. Primary data sources were obtained through interviews and direct observation of the Mekarwangi village, as one of the villages that received the program. Secondary data sources were obtained through literature study and documentation. This study used thematic analysis to analyze qualitative data from the results of interviews and observations made. The results concluded that Desa Berdaya Program of Rumah Zakat had succeeded in increasing 55% of beneficiaries (mustahiq) to become entrepreneurs, farmers, and breeders who have a steady income and continue to increase. However, this success was slow since it took seven years of coaching rather than four. Keywords: effectiveness, productive zakat, Desa Berdaya program, Rumah zakat